Artificial Intellegence (AI) dan Dampaknya Dalam Distorsi Pendidikan Islam - Faisol Hakim; Ahmad Fadlillah; M. Nafiur Rofiq (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This study explores the negative impacts of artificial intelligence (AI) in the context of Islamic education, with a focus on distortions in religious understanding, curricula, and interactions between students and teachers. Employing a qualitative research method and analyzing the works of Islamic education experts, the findings indicate that the use of artificial intelligence in Islamic education can result in distortions in the understanding of religious values, a loss of student creativity, and significant changes in the role of teachers and the learning environment. Using AI in Islamic education presents ethical challenges and the risk of distorting the interpretation of religious texts. Therefore, the recommendation from this research is the necessity of strict supervision and the development of ethical guidelines in implementing AI technology in Islamic education. This will help preserve religious values' integrity while harnessing technology's positive potential for religious understanding. The findings of this research offer valuable insights for Islamic education practitioners and policymakers by emphasizing the importance of maintaining religious values in the modern technological era. The negative impacts of AI use in Islamic education, such as the distortion of religious understanding and the loss of student creativity, underscore the urgency of adjusting AI implementation to mitigate risks and ensure the continuity of high-quality religious education